PENGARUH KEMANFAATAN, KEMUDAHAN PEMAKAIAN DAN KOMPETENSI AUDITOR PADA KEBERHASILAN PENERAPAN TEKNIK AUDIT BERBANTU KOMPUTER - Putra Wedantha, Pande Made; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi, 2016)
This study was conducted to prove the effect of usefulness, ease of use and the competence of the auditors on the successful application of computer-assisted audit techniques. The location of this research is in the Public Accounting Firm, which is listed on the Indonesian Institute of Certified Public Accountants region of Bali in 2014. The method of determining the sample in this study us e nonprobability sampling method. The technique used is purposive sampling technique and obtained 43 samples were used for analysis. Data collection method in this research using questionnaires and analysis techniques u s e multiple linear regression techniques. Based on the analysis, it is known that the usefulness, ease of use and the competence of auditor s have a positive and significant impact on the success of the application of computer-assisted audit techniques.
Keywords: usefulness, ease of use, the competence of auditors, the successful application of computer-assisted audit technique.